Does multinational ownership affect firm survival in Italy? - Ferragina, Anna Maria; Pittiglio, Rosanna; Reganati, Filippo (Journal of Business Economics and Management, 2014)
The aim of this paper is to investigate whether and how multinational status and foreign ownership affect the survival of Italian manufacturing and service firms. To this end, we analyze firm survival by distinguishing Italian firms as foreign multinationals (FMNEs) domestic multinationals (DMNEs) or domestic non-multinational firms (NMNEs). The empirical analysis is based on the Kaplan-Meier survival estimator and on the Cox proportional hazard model, in which we look for the impact of ownership dummies on firm survival, controlling for several firm and industry specific covariates. Our findings reveal that manufacturing and service firms owned by foreign multinationals are more likely to exit the market than either DMNEs or NMNEs. Moreover, DMNEs show a higher chance of survival in services. By decomposing firm activities into different technological classes, we also find that foreign ownership still exerts a negative influence on firm survival in both static and dynamic industries, while domestic multinationals in less-knowledge-intensive services appear more persistent.